Desenvolvimento de modelos biomecânicos para análise de tensões em pinos intrarradiculares biológicos - Artur Henrique de Freitas Avelar (2012)
Different types of fractures in teeth need especific treatments. In case of severe crown structure loss, the use of an intrarradicular post is necessary; this endodontic treatment is done for decades and still causes much discussion on how to improve the tecnique, the materials used and the consequences of long-term use. One of the latest innovations in the area is the research with posts of dentin, a material that would be ideal to fill the space of a root canal because it has similar mechanical properties to the root and better biocompatibility. With the increasing difficulty in obtaining human teeth, a replacement would be the bovine teeth for ease of obtaining, possessing large sizes and also having mechanical properties very similar to human teeth. After researches in order avaliate the mechanical properties of human and bovine dentin posts, this study proposes to create and avaliate three-dimensional mathematical models of the tensile test and compression at 135º test and validate previous results obtained in the laboratory. A tensile test model was created and simulated with finite element to build the stress-strain curve and analyzed how the non-linear elastic modulus of dentin influenced on the methodology and search for results, and how the region of data collection can create a stress-strain curve not true to reality. For the compression test at 135°, it was built a three-dimensional model of a canine tooth treated endodontically with materials such as composite resin, resin cement and periodontal ligament. After the construction of the model, the simulations of the tests were performed to validate the force-time curves to finally analyze the stress distributions along the tooth, and to see that the use of posts can create biological stress in places that, if there are fractures, they can appear in regions where it is possible for the dental surgeon to fix the tooth with a new post and does not require a more radical treatment such as tooth extraction and realization of a dental implant. In conclusion, the work could validate the mechanical tests that set out to do and could do a deeper analysis of the stresses that occur during the experiments.